Clinicopathological study of skin tumours - Shrivastava, Vaidik; Tangde, Ashwini; Joshi, Anil; Bindu, Rajan (International Journal of Research in Medical Sciences, 2019)
Background: Skin cancers are relatively uncommon malignancies worldwide, but the incidence of skin cancers has progressively increased over the last few decades. The distinction between benign and malignant neoplasm are more difficult to define when they appear in skin than when found elsewhere and histopathological examination is frequently required to establish a definitive diagnosis. Diagnosis of any skin tumours can be done by correlating clinical features and histological features. The aim and objective were to study age-sex wise distribution, clinical presentation and histopathological spectrum of various skin tumours. Methods: This is a retrospective study of three years conducted in the Department of Pathology, Government Medical College, Aurangabad, India from December 2015 to December 2018. Specimens received from Department of Dermatology were fixed in formalin and after adequately processing the sections were stained routinely with H and E stain and properly evaluated for histopathological examination. This study includes tumors of epidermis along with melanogenic tumors and skin appendageal tumors. The data collected was tabulated, analysed and compared to other similar studies. Results: The study consists of 130 cases. The ratio of male to female was 1.24:1. Head and neck region (48.46%) was the most common site observed where skin lesions were present followed by extremities (37.69%). Most of the malignant tumours were presented with non-healing ulcers (30.76%) and Noduloulcerative lesions (20.33%). Out of 130 cases, 83 (63.84%) were benign whereas 47 (36.15%) were malignant tumour. According to WHO classification, keratinocytic tumour 55 (42.30%) was the most common tumour type in the present study. Skin adnexal tumours and melanocytic tumours were observed in 54 (41.53%) and 21 (16.15%) respectively. Conclusions: The skin is a complex organ. Because of complexity of skin, a wide range of diseases can develop from the skin. The majority of benign neoplasms are from skin adnexal group whereas most common malignant neoplasm were from keratinocytic group. Skin adnexal tumors can occur anywhere in the body, however head and neck region constitute the most common site. Skin adnexal tumours are clinically often misdiagnosed, so histopathological examination remains gold standard for their correct diagnosis and for their differentiation between benign and malignant neoplasm.